2012
DOI: 10.1016/j.marpol.2011.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Whitefish wars: Pangasius, politics and consumer confusion in Europe

Abstract: Rapid growth in production of the farmed Vietnamese whitefish pangasius and its trade with the European Union has provoked criticism of the fish's environmental, social and safety credentials by actors including WWF and Members of the European Parliament and associated negative media coverage. This paper reviews the range of claims communicated about pangasius (identified as a form of mass mediated risk governance), in light of scientific evidence and analysis of data from the EU's Rapid Alert System for Food … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
45
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 28 publications
0
45
0
Order By: Relevance
“…According to Anh et al (2010), redundant feed contributes most to the generation of waste sludge in pangasius production. Moreover, the market for cheap white fish products, such as pangasius, is competitive because many possible substitutes are available (CBI, 2015;Little et al, 2012;Troell et al, 2014). Vietnamese pangasius products have gained a large market share in international markets because of their relatively low price (Bush & Belton, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…According to Anh et al (2010), redundant feed contributes most to the generation of waste sludge in pangasius production. Moreover, the market for cheap white fish products, such as pangasius, is competitive because many possible substitutes are available (CBI, 2015;Little et al, 2012;Troell et al, 2014). Vietnamese pangasius products have gained a large market share in international markets because of their relatively low price (Bush & Belton, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Its input and processing components employ over 180,000 persons directly, often women. Its development over the last two decades, as well as the associated controversies, such as environmental, social, and safety issues, have been well documented (e.g., Bosma et al ; Phan et al ; Bui et al ; De Silva et al ; Nguyen ; Bosma et al ; De Silva and Phuong ; Little et al ).…”
mentioning
confidence: 99%
“…However, if there is sufficient enforcement and regular audits by certification schemes, there is no reason why consumers cannot have absolute confidence in imported products, as well as those produced locally as there is clear provision of chain of custody from producer to retailer. Little et al (2012), showed that on the basis of RASFF notifications, the safety of farmed Asian seafood being imported into the EU was at least as good as that coming from capture fisheries, and communications with Asian aquafeed producers showed their awareness of the rules on intra-species feeding.…”
Section: Aquaculture Stewardship Council (Asc)mentioning
confidence: 99%